Multiethnic Settlement Segregation (A Case Study: Kampung 3-4 Ulu Laut in Palembang City - Endy Agustian; Rini Rachmawati; R Rijanta; Agus Joko Pitoyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to reveal the segregation pattern of multiethnic settlements in Kampung 3-4 Ulu Laut in Palembang City. The research method used in this study is a case study by means of in-depth interviews, observations, and documents. The results showed that the settlement pattern in Kampung 3-4 Ulu Laut Palembang City formed a colonization pattern or clustered at the front of the kampung due to the presence of there is a strong kinship base among people of Palembang descent who come from the same kinship lineage, such as the Palembang native ethnic, the Palembang Chinese ethnic and the Cirebonese Palembang ethnic. Meanwhile, at the back of kampung, the settlement pattern forms a spreading pattern and is more intended for immigrants ethnic who come from areas outside the Palembang City due to socioeconomic factors. The segregation of the settlements is a reflection of each ethnic groups in a settlement area which is supported by differences in economic, social, cultural, ethnic, and racial conditions. This separation is very visible in the position of the distribution of settlements from ethnic groups that form colonies on the front and back of Kampung 3-4 Ulu Laut. The existence of segregation of settlements in Kampung 3-4 Ulu Laut can be concluded that the settlement patterns that are formed reflect the inequalities that occur within an area, especially in the dominant groups in this case are the people of Palembang descent.